The Effect of Digitalization and Covid-19 Pandemic on Youth Unemployment in Indonesia - Arifin Arifin; Unggul Heriqbaldi (Yayasan Riset dan Pengembangan Intelektual, 2023)
The high rate of youth unemployment in Indonesia is a serious issue that needs to be addressed because it disrupts the national economic resurgence and disrupts the ongoing demographic bonus. Meanwhile, the younger generation is facing changes in the business model in the labor market due to technological advancements and digitalization. This research aims to analyze the impact of digitalization and the Covid-19 pandemic on the youth unemployment rate in Indonesia. The study uses panel data from 34 provinces in Indonesia covering the period from 2013 to 2022 and is estimated using the System Generalized Method of Moments (SysGMM) method. The results show that the development of digitalization, proxied by the Information and Communication Technology Development Index (IPTIK), has a positive and significant impact on the increase in youth unemployment. Similarly, the Covid-19 pandemic also has a positive and significant impact on the youth unemployment rate. Digitalization and the Covid-19 pandemic together indicate that the younger generation in Indonesia is vulnerable to economic and technological changes. Therefore, appropriate policies are needed to manage technological developments and address the impact of the pandemic so that the younger generation can be actively involved in the labor market. The results also show that control variables such as economic growth, inflation, and investment have varied effects on youth unemployment. Economic growth has a negative impact, in line with Okun's Law, while inflation does not significantly affect the youth unemployment rate. Investment has a negative and significant impact, indicating that increased investment can reduce youth unemployment in Indonesia.